Eating disorders between male and female adolescents with type 1 diabetes mellitus in Korea - Hye-Ryeon Park; Na-Geong Kim (Belitung Raya Foundation, Indonesia, 2022)
Background: Diabetes mellitus and its prevalence are rising dramatically in Korea and throughout the world, not only in adults but in adolescents. Objective: This study aimed to identify the sex-specific factors that influence eating disorders in adolescents with type 1 diabetes. Methods: A secondary analysis of a descriptive survey was employed. Raw data from 136 adolescents aged 13 to 18 years who were diagnosed with type 1 diabetes were obtained in the original study using the Diabetes Eating Problem Survey-Revised (DEPS-R), Rosenberg Self-Esteem Scale (RSES), and Beck Depression Inventory-II(BDI-II). The data were analyzed using the independent t-test and multiple regression analysis. Results: The female and male participants with eating disorders scored 21.67 ± 11.70 and 13.15 ± 8.03 points, respectively. Among the adolescents with type 1 diabetes, the factors related to eating disorders in female participants were body image satisfaction (β = 0.48, p <0.001) and depression (β = 0.22, p = 0.043), accounting for 33.4% of the variance. While the factors related to eating disorders in the male participants were BMI (β = 0.33, p = 0.006) and depression (β = 0.28, p = 0.017), accounting for 17.4% of the variance. Conclusion: Sex-specific factors should be considered to induce healthy eating behavior in adolescents with type 1 diabetes and reduce eating disorders. Moreover, it is necessary for female adolescents to perceive their body type accurately, and male adolescents need exercise and nutrition education to lower their body mass index. Collaborations between medical practitioners, changes in the medical environment, and social interests are necessary. Since depression is the common factor associated with eating disorders in female and male adolescents with type 1 diabetes, a periodic depression screening test and intervention program that can lower depression should be developed. At the government level, it is necessary to strengthen economic support for cost interventions.